Controlled release studies of 5-Fluorouracil through poly (vinyl caprolactum-co-vinyl acetate) microspheres - Yerriswamy, B; Reddy, C Lakshmi Narayana; Prasad, C Venkata; Subha, M C S; Rao, K Chowdoji; G, Venkatareddy (Asian Journal of Pharmaceutics (AJP), 2014)
Novel poly (vinyl caprolactam-co-vinyl acetate) microspheres were crosslinked with N’, N’ methylene bisacrylamide (NNMBA) prepared by free radical emulsion polymerization. This was done by using vinyl caprolactam, vinyl acetate, and NNMBA with varying amounts. 5-Fluorouracil (5-FU) is an anticancer drug which was mixed into these microspheres during in situ polymerization. These microspheres were characterized by using differential scanning calorimetry (DSC), X-ray diffraction (XRD), and scanning electron microscopy (SEM) techniques. XRD and DSC results indicated that there was uniform distribution of 5-FU drug particles in microspheres, and SEM pictures suggest that the microspheres are in spherical shape. Both encapsulation efficiency and release patterns are found to be dependent on the amount of crosslinking agent and amount of drug loaded. From the results of drug release kinetic studies, an anomalous and nonFickian behavior was observed in the present studies. Furthermore, in vitro release studies indicated the release of 5-FU up to 10 hours.